Functions and Authorities of the Armed Forces of Ukraine on the Crime Scene - Y. V. Grinenko (Bulletin of Kharkiv National University of Internal Affairs)
The functions and powers of the Armed Forces of Ukraine in the field of combating crime are researched. The expediency and necessity of studying the functions and powers as structural elements of the administrative and legal status of the Armed Forces of Ukraine is emphasized, which is especially relevant in connection with the reform of the Armed Forces of Ukraine and bringing their service activities to NATO standards.